A Description of Medication Decision-Making, Dispensing, and Utilization for Hypertensive Patients in Nishtar Hospital Multan, Pakistan - Hafiz Muhammad Khawar Saeed; Naveera Nasar; Sonia Batool; Rabia Ghauri; Aquula Rauf (University of Minnesota Libraries Publishing, 2013)
Hypertension is a worldwide health problem affecting developed and developing countries, and Pakistan is no exception. Nishtar Hospital Multan is categorized as one of the biggest hospitals in South Asia. The objective for this study was to describe medication decision-making, dispensing, and utilization for patients diagnosed with hypertension at this patient care facility. The study was conducted by 5 trained pharmacists working in collaboration with prescribers who met with study participants when they visited the hospital. All interview questions were asked in Urdu during the hospital visit. Data were summarized using descriptive statistics. A total of 301 patients who visited the hospital agreed to participate in the study. The findings showed that prescribers spend little time with patients and rarely follow guidelines for decision-making. Regarding the dispensing of medications for the treatment of hypertension, none of the dispensing was completed by a pharmacist and none of the patients received counseling about medications at the time of dispensing. Most patients reportedly do not take their medication as prescribed. Regarding outcomes, 20% of the patients had pre-hypertension, 47% stage 1 hypertension, and 33% stage 2 hypertension. Great improvements are possible in the treatment of hypertension at the hospital we studied through application of standard treatment guidelines, patient education, and adjustments to work system processes so that alignment of provider's skills with opportunities in improving the patient care process can be achieved.   Type: Case Study